Mythe. - Aerts, Egbert; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1989)
Devreux, Pierre ; De Wilde, Karlos ; Minnaert, Frans ; Monteyne, Roland ; Niels, Eddy ; Poot, Rik ; Tanghe, Marijke ; Van Damme, Fritz ; Van Ransbeeck, Agnes ; Van Wijnendael, Sylvain
Mythe, Hof ter Nederloo, Sint-Pieters-Leeuw, 3 februari - 12 maart 1989
boek